2012
DOI: 10.1038/gim.2011.66
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences regarding the return of individual genetic research results: findings from a qualitative focus group study

Abstract: Introduction Studies have found that people are interested in receiving their individual research results (IRRs) in exchange for participating in genetic studies. However, it is unclear whether the public understands the nature and limitations of these results and whether they would want information with little or no clinical utility. Methods We conducted 10 focus groups in three U.S. cities to examine the types of results they would want to learn, the perceived value of results with little or no clinical ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
204
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(232 citation statements)
references
References 25 publications
(30 reference statements)
24
204
1
Order By: Relevance
“…We have previously published the results of our focus groups with participants of this DNA biobank, who were primarily Hispanic and African American, and found that the reasons expressed for participation were similar to those previously reported in primarily White biobank participants, particularly altruism and an expectation of personal health benefit (Streicher et al 2011). As noted by others, quantitative data on this topic would be useful to complement the previous qualitative studies that have been conducted (Bollinger et al 2012). Our aims in the present study were therefore as follows:…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…We have previously published the results of our focus groups with participants of this DNA biobank, who were primarily Hispanic and African American, and found that the reasons expressed for participation were similar to those previously reported in primarily White biobank participants, particularly altruism and an expectation of personal health benefit (Streicher et al 2011). As noted by others, quantitative data on this topic would be useful to complement the previous qualitative studies that have been conducted (Bollinger et al 2012). Our aims in the present study were therefore as follows:…”
Section: Introductionsupporting
confidence: 67%
“…A handful of studies addressing interest in receiving personal results specifically from genomics research in diverse populations using a focus group methodological approach have recently been conducted (Bollinger et al 2012;O'Daniel and Haga 2011). One of these studies suggested that individuals from diverse backgrounds seem interested in receiving personal results from genomics research (Bollinger et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be counterbalanced by an increased emphasis on the uncertainty associated with almost all genetic variants. Such an approach would be consistent with recent consensus statements (e.g., National Cancer Institute 2010) and empirical reports (e.g., Bollinger et al 2012) that downplay the importance of "actionability." Nor would all reportable variants need to be as certain, or associated with a condition as severe, as the mutation causing Huntington disease.…”
supporting
confidence: 70%
“…In addition, individual results may be offered results if other conditions are met (National Heart Lung Blood Institute working group et al 2010). Since then, studies have identified support for disclosing personal genomic results from genomic study participants (Allen et al 2014;Bollinger et al 2012;Halverson and Ross 2012;Overby et al 2015;Trinidad et al 2015), researchers (Appelbaum et al 2015;Meacham et al 2010), IRB committee members (Beskow and O'Rourke 2015;Dressler et al 2012), ethicists and lawyers (Burke et al 2014;Evans 2014;Thorogood et al 2014;Wolf et al 2015), and two genomics research networks ). In addition, NHLBI (2010) recommended that Binvestigators conducting research with identifiable communities should engage the community on the return of aggregate and/or individual research results^, and other researchers concurred (Lemke et al 2012;Marsh et al 2013;Overby et al 2015;Trinidad et al 2015).…”
Section: Discussionmentioning
confidence: 99%